Diagnosis dan tatalaksana terbaru penyakit pleura - Pranita, Ni Putu Nita (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Pleural effusion is a common problem. Pleural effusion developed as a sequel to the underlying disease process, including pressure/volume imbalance, infection, and malignancy. In addition to pleural effusion, persistent air leak after surgery and bronchopleural fistula remain a challenge by a physician. An understanding of the pleural disease, including its diagnosis and management, has made an extraordinary step. The introduction of molecular detection of organism-specific infections, risk stratification, and improvement in the non-surgical treatment of patients with pleural infection are all within reach and maybe the standard of care shortly. This article discusses the role of existing techniques, and some of the more recent ones, which are now available for establishing the diagnosis of pleural disease. The initial approach to diagnosis usually begins by distinguishing between transudates and exudates, based on the concentration of protein and lactate dehydrogenase (LDH) in pleural fluid. The exact role of amylase and LDH can provide additional information towards the differential diagnosis of various exudative pleural effusions. With newer cytochemical staining techniques in pleural fluid, diagnostic results of malignant pleural effusion can increase by up to 80%. Ultrasound (US) and thoracic computed tomographic (CT) scans have further improved the diagnosis of undiagnosed pleural effusion. The reappearance of thoracoscopy as the latest diagnostic and therapeutic tool (e.g., Pleurodesis) for undiagnosed or recurrent pleural effusions. Management of malignant pleural effusion continues to develop with the introduction of tunneled pleural catheters and chemical pleurodesis procedures. Advances in the diagnostic and therapeutic evaluation of pleural disease and what appears to be an increasing multidisciplinary interest in a doctor managing patients with pleural disease.